Antioxidant and antimicrobial effects of kordoi (Averrhoa carambola) fruit juice and bamboo (Bambusa polymorpha) shoot extract in pork nuggets. (1st January 2016) - Thomas, R.; Jebin, N.; Saha, R.; Sarma, D.K.
Highlights: Pork nuggets with 'very good' acceptability were processed by incorporating kordoi fruit juice and bamboo shoot extract. We examine quality changes of nuggets during refrigeration temperature storage. Addition of extracts and juice has improved the microbiological quality, sensory parameters and has reduced the lipid oxidation. We report an increase of shelf life of pork nuggets from 21 days to 35 days at refrigeration storage. Abstract: Pork nuggets with 'very good' acceptability was processed by incorporating kordoi ( Averrhoa carambola ) fruit juice and bamboo ( Bambusa polymorpha ) shoot extract, and their physical, chemical, microbiological and sensorial characteristics were evaluated during 35 days storage under refrigeration. Addition of kordoi fruit juice (4%) and bamboo shoot extract (6%) had a significant effect on the pH, moisture, protein, fat, fiber, instrumental color values and texture profiles of nuggets. Nuggets with juice and extract had significantly lower TBARS values towards the end of the storage period compared to the control. Microbial and sensory qualities of nuggets were significantly improved by the addition of juice and extract. Incorporation of juice and extract at 4% and 6% levels, respectively, increased the storage life of pork nuggets by at least two weeks, i.e. from 21 days to 35 days at 4 ± 1 °C compared to the control.